How to make great decisions - Vander Mey, Chris (O'Reilly, 2018)
Unfortunately, making decisions is not as simple as you saying "yes" or "no" to your team. Unlike most other compilations of English words, the complexity of software mandates that it is the creation of a group, and therefore it is a reflection of the decisions that the group makes. In some cases a Big Boss can dictate decisions. Unluckily, you are not the Big Boss, and you must enable your team to find ways to say no to the things they love. Here's how to get the job done.